The vegetation of the Iberian Peninsula. Volume 2 - Loidi, Javier (Springer, 2017)
This book provides a compact, up-to-date and detailed overview of the vegetation of the Iberian Peninsula, a highly diverse part of Europe in the Mediterranean area. Written by a group of experienced researchers, the volume includes a first section with general chapters discussing the climate, the biogeography and the flora, and a second section with detailed descriptions of the 14 regional sectors into which the peninsula and Balearic Islands have been divided. A third section explores special features, such as aquatic vegetation, gypsum and dolomite vegetation, coastal vegetation, mountain flora and vegetation, conservation issues and alien flora.
Includes indexes.
Keywords: Plants -- Iberian Peninsula.; Europe -- Iberian Peninsula.; elektronické knihy; electronic books